Evolution and update on current devices for prosthetic breast reconstruction - O’Shaughnessy, Kristina (Gland Surg, 2015)
Over the past decade, the leading breast reconstruction modality has shifted from autologous tissue to implants. This trend reversal is multi-factorial but includes increasing bilateral mastectomies and the more widespread acceptance of implants due to stringent quality and safety regulatory surveillance by the US Food and Drug Administration (FDA). Since 2012, the US FDA has approved several new implant styles, shapes and textures, increasing the choices for patients and surgeons. Predictable, superior aesthetic results after prosthetic breast reconstruction are attainable, but require thoughtful planning, precise surgical technique and appropriate device selection based on several different patient and surgeon parameters, such as patient desires, body mass index, breast shape, mastectomy flap quality and tissue based bio-dimensional assessment. This article briefly reviews historic devices used in prosthetic breast reconstruction beginning in the 1960s through the modern generation devices used today. We reflect on the rigorous hurdles endured over the last several decades leading to the approval of silicone gel devices, along with their well-established safety and efficacy. The various implant characteristics can affect feel and performance of the device. The many different styles and features of implants and expanders are described emphasizing surgical indications, advantages and disadvantages of each device.